MENINGKATKAN KEMAMPUAN TATA CARA BERWUDHU’ MELALUI MEDIA KARTU KATA BERGAMBAR PADA ANAK TUNAGRAHITA SEDANG - Esi Esi (Jurnal Penelitian Pendidikan Khusus, 2012)
The research was done on a child being X class II Tunagrahita in Bukittinggi Ganting SDLB State Mangosteen, from observations in children encountered wudu incomplete pass, and has not been uniform. Thus the researchers want to improve washing pollutes the media picture word cards. Once the data is analyzed, the percentage obtained ablution Rather, they are good at the baseline condition was 45.83%, indicating the ability of wudhunya Rather, they are still low. While the percentage of state intervention ablution Rather, they are obtained is 87.5% meaning that the child's ability to perform ablutions pollutes considerably increased. At baseline conditions ablution Rather, they change the level is 25% (+) means to indicate a positive direction that the percentage of ablution Rather, they acquired during baseline conditions slightly increased but the percentage is still low. As for the intervention rate is 50% perubahanya level (+) means indicates a positive direction that the percentage of ablution Rather, they are obtained in much improved during the intervention condition compared to baseline conditions. As for the percentage overlapenya gained as much as 0%, meaning that the smaller the percentage overlape the better the effect of interventions on the target behavior.